Antidiarrhoeal Activities of Lime (Citrus aurantiifolia) Extract in Experimentally-Induced Diarrhoea Model - Isirima, Joshua Charles; Uahomo, Precious Ojo (Biology, Medicine, & Natural Product Chemistry, 2023)
This study investigated the effects of Lime on Diarrhoea in Wistar rats. A total of 60 Wistar rats were procured and randomly divided into 3 groups of 20 animals each for each of the three t-test models. The twenty healthy Wistar rats for each diarrhoea model were fasted for 6 hours prior to the experiment but allowed free access to water. The twenty animals were randomly divided into 5 groups of 4 animals each for each experiment. Established antidiarrhea models were followed. The test groups received various doses (97.65mg/kg, 195.3mg/kg, and 390.6mg/kg) of Citrus aurantiifolia juice extract; whereas positive controls received Loperamide (2.5mg/kg) and negative controls received distilled water (1ml/kg). The administration was done once daily for 15 days, and the faeces of each animal was collected on the 5th, 10th and 15th day. The result of this study showed that medium and high dose Citrus aurantiifolia has an anti-diarrhoeal effect on castor oil-induced diarrhoea over repeated administration for a minimum of 15 days as it prolonged the onset of diarrhoea, decreased the frequency of defecation and gastrointestinal transit time in Wistar rats. This study shows that Citrus aurantiifolia demonstrates significant anti-diarrhoeal activity and can be used as an anti-diarrhoea agent.